HOMA‐IR as a risk factor of gestational diabetes mellitus and a novel simple surrogate index in early pregnancy - Song, Shuoning; Zhang, Yuemei; Qiao, Xiaolin; Duo, Yanbei; Xu, Jiyu; Peng, Zhenyao; Zhang, Jing; Chen, Yan; Nie, Xiaorui; Sun, Qiujin; Yang, Xianchun; Lu, Zechun; et al. (International journal of gynecology and obstetrics, 2022)
Objective To assess the association between insulin resistance and gestational diabetes mellitus (GDM) in early pregnancy and find a simple surrogate index of the homeostasis model assessment of insulin resistance (HOMA‐IR). Methods A total of 700 pregnant women were included in this prospective, double‐center, observational cohort study. The glucose and lipid metabolic characterization was performed at 6–12 weeks of pregnancy. All participants underwent a 75‐g oral glucose tolerance test at 24–28 weeks of pregnancy. Linear regression analysis was applied to find a novel surrogate index of HOMA‐IR. Binary logistic analysis was applied to estimate possible associations of different indices with GDM and insulin resistance. Results GDM was diagnosed in 145 of 700 women with singleton pregnancies (20.7%). HOMA‐IR was higher in the GDM group than in the normal glucose tolerance (NGT) group and was an individual risk factor for GDM (adjusted risk ratio RR 1.371, 95% confidence interval [CI] 1.129–1.665, P < 0.001). TyHGB index as the surrogate index of HOMA‐IR was represented as TG/HDL‐C + 0.7*FBG (mmol/L) +0.1*preBMI (kg/m2)(where TG/HDL‐C is triglyceride/high‐density lipoprotein cholesterol; FBG is fasting blood glucose, and preBMI is the pre‐pregnancy body mass index [calculated as weight in kilograms divided by the square of height in meters]). The cut‐off point of the TyHGB index was 6.0 (area under the curve 0.827, 95% CI 0.794–0.861, P < 0.001) for mild insulin resistance. Conclusion Increased HOMA‐IR in early pregnancy was a risk factor of GDM. TyHGB index could be a surrogate index of HOMA‐IR and had a predictive value for GDM.